Epigenetic targets to enhance antitumor immune response through the induction of tertiary lymphoid structures - Omotesho, Quadri Ajibola; Escamilla, Alejandro; Pérez-Ruiz, Elisabeth; Frecha, Cecilia A.; Rueda-Domínguez, Antonio; Barragán, Isabel (Frontiers in Immunology, 2024)
Tertiary lymphoid structures (TLS) are ectopic lymphoid aggregates found in sites of chronic inflammation such as tumors and autoimmune diseases. The discovery that TLS formation at tumor sites correlated with good patient prognosis has triggered extensive research into various techniques to induce their formation at the tumor microenvironment (TME). One strategy is the exogenous induction of specific cytokines and chemokine expression in murine models. However, applying such systemic chemokine expression can result in significant toxicity and damage to healthy tissues. Also, the TLS formed from exogenous chemokine induction is heterogeneous and different from the ones associated with favorable prognosis. Therefore, there is a need to optimize additional approaches like immune cell engineering with lentiviral transduction to improve the TLS formation in vivo. Similarly, the genetic and epigenetic regulation of the different phases of TLS neogenesis are still unknown. Understanding these molecular regulations could help identify novel targets to induce tissue-specific TLS in the TME. This review offers a unique insight into the molecular checkpoints of the different stages and mechanisms involved in TLS formation. This review also highlights potential epigenetic targets to induce TLS neogenesis. The review further explores epigenetic therapies (epi-therapy) and ongoing clinical trials using epi-therapy in cancers. In addition, it builds upon the current knowledge of tools to generate TLS and TLS phenotyping biomarkers with predictive and prognostic clinical potential.